Professionalization of the voluntary sport sector : case Helsingin Palloseura - from Finnish champions to local youth development - Annala, Olli (2019)
Professionalization in sport is an increasingly studied topic in the field of sport sciences. The focus of the scholars has been especially on the voluntary sport sector of which several case studies of sport federations have been published. However, there is a need for more case studies, also of the voluntary sport clubs, to better validate the theoretical frameworks in the field. The recent developments in the voluntary sector make it an interesting area for research. The changing role of the voluntary sport clubs only adds to the interest. By better understanding the operational environment of the voluntary sport clubs, it could be possible to make them more efficient and successful in their operations, thus benefitting the vast amounts of members of the clubs, and the society in general. The aim of this study was to add to our understanding of the operational environment of a voluntary sport club in the process of professionalization. The objectives to achieve this aim were to study professionalization in the voluntary sport sector, and specifically to analyse the recent professionalization process of the football club Helsingin Palloseura. The organizational culture and the operations of HPS as well as the changes and challenges regarding them were under the spotlight. The data for this case study was collected in two focus group interviews, one with four current and former chairmen and members of the board of the club and the other with three longest-serving staff members of the club. The interviews were analysed by using qualitative content analysis, and the findings were combined with the theoretical models and frameworks reviewed. Based on the analysis, a model of professionalization for voluntary sport clubs was proposed. The main finding of the study was the importance of the commitment of the chairman and the board members in the professionalization process of a voluntary sport club, especially in the initiation of the process. Likewise, it became evident that shared leadership becomes increasingly important as the voluntary sport club begins to hire paid employees. The importance of quality orientation cannot be overstated, either. In an operational environment where resources are scarce, efficient cooperation and quality operations are all important.